Booksellers and Printers in Provincial France 1470-1600 - Walsby, Malcolm, author.
1 online resource.
Keywords: Booksellers and Printers in Provincial France 1470-1600 is the first comprehensive guide to the Renaissance French book trade outside of Paris and Lyon. This volume presents short biographies for over 2700 booksellers, printers and bookbinders - over sixty of whom are identified as fictitious. The biographies are accompanied wherever possible by the details of commercial partnerships, the type used by printers and reproductions of over a hundred signatures. The book provides the details of over 600 women who either married into the trade or were independently active. The introductory essay analyses the nature, evolution and geographic dispersion of the members of the trade. It is an indispensable tool for understanding the French Renaissance book world.